Biodiversity of West African forests : an ecological atlas of woody plant species (CABI, 2004)
This book focuses on the biodiversity and ecology of West African forests. The first part of the book includes 8 chapters which analyse the factors that give rise to biodiversity and structure tropical plant communities. It emphasizes the distribution and state of the forests and analyses vegetation gradients, determines hotspots of plant diversity, and treats distribution patterns of rare and endemic species in the Upper Guinean forests which extend from Senegal to Togo. The main part of the book is an atlas with ecological profiles of 280 rare and endemic plant species and 56 large timber species, each with a one-page entry including a coloured photograph and distribution map. This book will appeal to researchers working in forestry, biodiversity, plant ecology and conservation.